ANALISIS IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY UNTUK MENINGKATKAN REPUTASI PERUSAHAAN (STUDI PADA PT. KENCANA MAJU BERSAMA SURABAYA) - Brigita Aristya Eka; Bagus Cahyo Shah Adhi Pradana; Muchamad Rizqi (Sintesa, 2023)
Corporate Social Responsibility (CSR) is a program that is seen as a form of Corporate Social Responsibility to stakeholders and the environment in all aspects of the company. CSR is a new phenomenon in Indonesia, where CSR is an activity to pursue the Triple Bottom Line which consists of the 3P concept (Profit, People and Planet). Therefore, this writing aims to find out things related to the implementation of Corporate Social Responsibility (CSR) activities in one of the companies engaged in construction in Surabaya, namely PT. Kencana Maju Bersama which is connected with the 3P CSR concept in order to achieve its goal of increasing the company's reputation. The writing method used is qualitative and this writing consists of primary and secondary data sources. The writing results show that the implementation of the CSR process at PT Kencana Maju Bersama Surabaya is quite good, as evidenced by the fulfillment of all activities based on the public relations process according to Cutlip, Center, and Broom (2005) and also the 3P CSR concept according to John Elkington (1997). It can also be concluded that this CSR activity can improve the reputation of PT Kencana Maju Bersama Surabaya as this CSR activity progresses.